Suplementação de ácido guanidinoacético para matrizes suínas e suas progênies: desempenho dos leitões na fase de creche - Mendonça, Ingrid Barbosa de (2018)
The aim of this study was to evaluate the effects of guanidinoacetic acid supplementation to sows and their litter on blood parameters, performance and economic viability of piglets at nursery phase. A total of 80 high-prolific mixed-parity sows from 3rd and 4th parity orders were distributed between 2 treatments: control diet and supplemented diet with 0.1% of guanidinoacetic acid. Sows were fed with the dietary treatments during the gestation and lactation phases, until weaning. Piglets were weaned at 23 days of age and then distributed in a randomised block design, in a 2x2 factorial arrangement, considering 2 diets to sows during gestation and lactation (control and supplemented diet with 0.1% of guanidinoacetic acid) and 2 diets to piglets at nursery phase (control and supplemented diet with 0.1% of guanidinoacetic acid). Each treatment consisted of 6 replicates, being the pen with 40 animals considered as experimental unit. Dietary supplementation of guanidinoacetic acid to sows and their litter did not influenced performance and blood parameters of piglets during the nursery phase (P>0.05). Piglets fed supplemented diets showed the worst values in economics variables during total period (P<0.05). Guanidinoacetic acid supplementation to sows and their litters do not improve performance and economic viability of piglets at nursery phase.